2014
DOI: 10.1101/003673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geometry shapes evolution of early multicellularity

Abstract: Organisms have increased in complexity through a series of major evolutionary transitions, in which formerly autonomous entities become parts of a novel higher-level entity. One intriguing feature of the higher-level entity after some major transitions is a division of reproductive labor among its lower-level units in which reproduction is the sole responsibility of a subset of units. Although it can have clear benefits once established, it is unknown how such reproductive division of labor originates. We cons… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…These results are consistent with prior literature showing that loss-of-function mutations in this gene cause settling/clumping phenotypes in other experimental evolution scenarios (Voth et al 2005;Koschwanez et al 2013;Oud et al 2013;Ratcliff et al 2015). Furthermore, ace2 null mutants have the characteristic cell separation defect that we observed in our clones (Libby et al 2014;Ratcliff et al 2015). Using complementation with the wild-type allele, we verified that the ACE2 mutations were causative of the separation defect aggregation phenotype in these two clones (Table 1), with subtle modification to the cell morphology by BEM2-a gene involved in bud emergence that is also mutated in both clones ( Figure S2B in File S1) (Bender and Pringle 1991;Kim et al 1994).…”
Section: Majority Of Aggregating Clones Demonstrate Characteristics Osupporting
confidence: 94%
“…These results are consistent with prior literature showing that loss-of-function mutations in this gene cause settling/clumping phenotypes in other experimental evolution scenarios (Voth et al 2005;Koschwanez et al 2013;Oud et al 2013;Ratcliff et al 2015). Furthermore, ace2 null mutants have the characteristic cell separation defect that we observed in our clones (Libby et al 2014;Ratcliff et al 2015). Using complementation with the wild-type allele, we verified that the ACE2 mutations were causative of the separation defect aggregation phenotype in these two clones (Table 1), with subtle modification to the cell morphology by BEM2-a gene involved in bud emergence that is also mutated in both clones ( Figure S2B in File S1) (Bender and Pringle 1991;Kim et al 1994).…”
Section: Majority Of Aggregating Clones Demonstrate Characteristics Osupporting
confidence: 94%
“…Previous studies demonstrated that the elastic modulus of individual yeast cells is relatively constant with respect to cell size 16 ; if individual snowflake yeast cells behave similarly, the compressive modulus may be expected to increase if interior volume fraction increases 17,18 . It is important to note that the distribution of cells within clusters is very heterogeneous 7,19 ; cells in the cluster interior are much more crowded than those at the periphery (Fig. 1b,d).…”
Section: Nature Physicsmentioning
confidence: 99%
“…Indeed, this mechanism should be considered a viable hypothesis to be tested in future experiments examining novel experimental lineages. More generally, nascent multicellular organisms are expected to be heavily affected by physical effects arising from their spatial structure [3,5,22,23]. Within-cluster gradients of nutrients, waste products and even previously evolved signalling molecules (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…We modelled this effect quantitatively. The structure of a snowflake yeast cluster can be represented as a graph with a tree-like structure, in which cells are nodes and cell-cell connections are edges (figure 3a; [3,5]). Clusters reproduce when an edge is severed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation